ANALISIS KAUSALITAS PENERIMAAN PAJAK, PENGELUARAN PEMERINTAH DAN PERTUMBUHAN EKONOMI DI INDONESIA - Ibrahim Wira Sanjaya; Ali Anis (Universitas Negeri Padang, 2021)
This study aims to analyze the causality between tax revenue, governmentexpenditure and economic growth . This type of study is descriptive and associative. This study uses panel data from 1970-2019 covering 33 provinces in Indonesia. This study uses the PVAR analysis method and uses Granger Causality Test for causality test with tax revenue, government expenditure and economic growth as independent variables. The results of this study indicate that: (1) There is a one-way causality of the tax revenue variable on the government expenditure variable; (2) there is a one-way causality from the economic growthvariable to the government expenditure variable; (3) There is no causality between the tax revenue variable and the economic growth variable.